A historic view of the conceptual relations between theoretical and quantitative psychology - Dávila Dávila, Alex (1999)
This paper reviews the history of conceptual relations between theoretical and quantitative psychology. The concepts of mathematical psychology, psychometry, and their links to psychological structuralisms and functionalisms are reviewed. This work stresses the need of giving a psychological theoretical background to the quantitative point of view in psychology. Spearman's theory of intelligence is proposed as a model of synthesis between theoretical and quantitative psychology; it is proposed also to integrare psychometry with experimental psychology to proof psychological hyphotesis derived of psychomarhematical and psychostatistical frames.